Laboratory Studies on the Effects of the Entomopathogenic fungus Beauveria bassiana (Bals.) Vuill, on the Homaira insect, Batrachedra amydraula (Lepidoptera : Cosmopterygidae) - Aziz, Fawzia; Al-janabi, Suhaila; Na'ama, Rabab (Iraqi Journal of Science, 2023)
This study was conducted to evaluate the pathogenicity of Beauveria bassiana to the Homaira insect Batrachedra. amydraula under laboratory conditions. The dilution 1 x 10-2 showed a significant and high mortality rates on the eggs, first and fifth instars of the homaira larvae which reaches 100%, 96.19% and 91.20% after 7 days from treatment. However mortality rates found to be decreased to 88.97% for fifth instar after 10 days from treatment, while results showed parasitism potentially reaches 94.50% in pupae and 90.22% in adults.